The psychosocial development of world-class athletes: Additional considerations for understanding the whole person and salience of adversity - Gucciardi, Daniel (2017)
In the target article, Hardy and colleagues provided an incisive analysis of retrospectively reported psychosocial factors associated with the development and careers of 32 former athletes from Olympic sports. They found that Super-Elite athletes (serial medal winners at major international championships, i.e., World Championship or Olympic Games) differed from matched Elite performers (won medals at international competitions but not major championships) with regard to several important psychosocial factors (e.g., negative life events, turning point, relative importance of sport). In this commentary, I critique and extend upon these key findings to delineate additional considerations for understanding the whole person (i.e., traits, characteristic adaptations, narrative identity) and salience of adversity (i.e., timing, frequency, and duration) with the goal to stimulate future research and theory on the psychosocial development of Olympic champions.